Slinky Malinki - Dodd, Lynley (London : Puffin Books, 1992)
A verse description of the ambitious nocturnal thefts carried out by a prowling cat called Slinky Malinki.
Children's picture story book by a New Zealander.
"First published by Mallinson Rendel Publishers Ltd. Wellington, New Zealand, 1990"--Colophon.
"Mallinson Rendel."
For 4-6 year olds -- Education Services, Wellington, N.Z.
Keywords: Cats -- Fiction; Animals -- Fiction; Stories in rhyme